Adsorption sites, metal-support interactions, and oxygen spillover identified by vibrational spectroscopy of adsorbed CO: A model study on Pt/ceria catalysts - Happel, Markus; Myslivecek, Josef; Johanek, Viktor; Dvorak, Filip; Stetsovych, Oleksandr; Lykhach, Yaroslava; Matolin, Vladimir; Libuda, Jörg (Journal of Catalysis, 2012)
Vibrational spectroscopy of adsorbed CO is commonly used for the characterization of oxide-supported metal catalysts, in spite of persisting ambiguities concerning the band assignment. Here, we present reference data on well-defined Pt/CeO2(1 1 1)/Cu(1 1 1) model catalysts aiming at clear identification of the related features. Growth and morphology of the Pt particles are investigated by scanning tunneling microscopy (STM), the adsorption properties are probed by temperature programmed desorption (TPD), and the electronic structure has previously been studied by photoelectron spectroscopy (PES) and resonant photoelectron spectroscopy (RPES). Combining molecular beam (MB) methods and infrared reflection absorption spectroscopy (IRAS), we correlate this information to the interaction with CO.Two types of defect adsorption sites are identified on the ceria support (2097 cm(-1), 2120 cm(-1)), which are assigned to structural defects and reduced Ce3+ centers. The relative abundance of these sites changes upon thermal treatment. On the Pt nanoparticles, CO first adsorbs on-top at step and edge sites (2066 cm(-1)), before adsorption on the (1 1 1) facets occurs in bridging (1875 cm(-1)) and on-top (2080-2097 cm(-1)) geometry. For the first time, we identify vibrational CO features, which arise from electronic metal-support interactions and from oxygen reverse spillover. On reduced CeO2-x(1 1 1), a red-shifted band at 2053 cm(-1) appears, which is attributed to increased pi-backbonding from Pt to CO, as a result of a change in electronic metal-oxide interaction. Thermal treatment also activates oxygen reverse spillover from the support to the Pt nanoparticle, which gives rise to a blue-shifted feature in the CO spectrum (2090-2105 cm(-1)) due to coadsorbed oxygen next to CO sites. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Model catalysis; Cerium oxide; Platinum; Metal-oxide interaction; Carbon monoxide; Infrared spectroscopy; Scanning tunneling microscopy